Analisis Akuntabilitas dan Transparasi Pengelolaan Dana Bantuan Operasional Kesehatan (BOK) di Puskesmas Watubaing Kecamatan Talibura Kabupaten Sikka - Angelina Nona Lehan; Yosefina Andia Dekrita; Margaretha Yulianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The background in this research was that the use of Operational Assistance Funds program must be taken into consideration for accountable and transparent financial governance. The research aimed to determine the accountability and transparency of the management of health operational assistance funds at the Watubaing Public Healt Center in Talibura subdistrict, Sikka regency. The research method employed descriptive qualitative while the analysis tool was carried out through data collection using observation, interview, and documentation techniques. The research findings indicated that the implementation of accountability and transparency principles had been well implemented, as seen from the reporting mechanism according to the Operational Assistance Funds Technical Guidelines. The principle of transparency was quite open which can be seen from the initial planning openness of MINILOK and POA drafting system which involves all staff at the Watubaing Health Center and the cross-sector community.